Can Euroland survive? - Stephanie A. Kelton; L. Randall Wray (Levy Economics Institute of Bard College, 2009)
Social unrest across Europe is growing as Euroland's economy collapses faster than the United States', the result of falling exports and a weaker fiscal response. The controversial title of this brief is based on a belief that the nature of the euro itself limits Euroland's fiscal policy space. The nations that have adopted the euro face market-imposed fiscal constraints on borrowing because they are not sovereign countries. Research Associate Stephanie A. Kelton and Senior Scholar L. Randall Wray foresee a real danger that these nations will be unable to prevent an accelerating slide toward depression that will threaten the existence of the European Union.
Keywords: 330